Quantitative determination of trifuzol in the 2.5% injection solution by spectrophotometric method - N. N. Borisenko; K. P. Medvedev; S. A. Vasyuk; I. V. Bushueva; V. V. Parchenko (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The effectiveness of the treatment of common diseases of the respiratory system, hematopoietic system, digestive system of livestock and domestic animals with the help of existing drugs is not always sufficient, and there is an urgent need to expand the arsenal of domestic veterinary medicinal products that would exhibit antiviral, anti-inflammatory and low toxicity, prompted to search, create and improve existing veterinary medicines. A medicine in the form of a 2.5% injection solution containing, as an active substance, a 1,2,4-triazole derivative - piperidine 2-[5-(furan-2-yl)-4-phenyl-1,2,4-triazole-3-ylthio] acetate exhibits a fairly high level of anti-inflammatory, antiviral, and immunomodulating effects. The arsenal of domestic veterinary drugs with the above activity is currently limited. The analysis of veterinary medicinal products is the most important stage in the system for ensuring the quality control of medicinal products. During the entire storage period of the drug, various methods of identification and quantification of the active substances are needed. And despite the fact that spectrophotometry in the UV region is not very specific and selective, the expressness of these methods allows them to be widely used for routine quality control of drugs. Development and validation of a method for the quantitative determination of trifuzole in a 2.5% injection solution according to its own absorption. The study used a working standard sample of trifuzol 2.5% injection solution of trifuzol, as a solvent - purified water. Analytical equipment: Specord 200 spectrophotometer, electronic balance AVT-120-5DM. The aim of our work was the development and validation of a new, express method for the quantitative determination of trifuzol in the composition of a 2.5% injection solution in the UV region. The proposed method is based on measuring the optical density of an aqueous solution of a compound at 278 nm. The technique was successfully validated for such characteristics as linearity, precision, correctness, specificity and robustness, according to the requirements of HFCs. The analysis of the predicted total uncertainty of the analysis showed the reproduction of the method and the possibility of its application in other laboratories. The validation of the method for the quantitative determination of trifuzol in the composition of a 2.5% injection solution according to the requirements of HFCs was carried out. It is proved that according to such validation characteristics as linearity, specificity, precision, correctness and robustness, the technique is correct.